Таинство покаяния в православных приходах Севера России (XVIII – начало ХХ в.) ... : The sacrament of penance in the Orthodox parishes in the North of Russia (since the 18th century till the beginning of the 20th century) ... - Pulkin, Maxim Viktorovich (Ecological Safety and Balanced Use of Resources, 2019)
В статье рассмотрены специфические черты организации исповедного учета и осуществления таинства покаяния на Севере России. Выявлено, что отношение духовенства и мирян к исповеди заметным образом менялось на протяжении всего изучаемого периода. Материалы XVIII в. рисуют картину жесткого контроля над осуществлением таинства. Уклоняющиеся от исповеди повергались разнообразным формам преследования, в том числе денежным штрафам. Данные XIX в. показывают, что отношение церковной и светской власти к исповеди претерпело серьезные изменения. Отныне основу деятельности духовенства составляла проповедь, в том числе на карельском языке, нацеленная на то, чтобы убедить местное население в необходимости ежегодного покаяния. Оба варианта воздействия на мирян не принесли успеха, оказались малоэффективными. ... : The article discusses specific features of the organization of confessional accounting and the implementation of the sacrament of penance in the Russian North. It was revealed that the attitude of the clergy and laity to confession noticeably changed throughout the period under review. Materials of the 18th century paint a picture of the tight control over the implementation of the sacrament. Those who shy away from confession are subjected to various forms of persecution, including fines. Data of the 19th century show that the attitude of church and secular authorities towards confession has undergone major changes. From now on, the basis for the activities of the clergy was preaching, including in the Karelian language, aimed at convincing the local population of the need for annual repentance. Both versions of the impact on the laity did not bring success and were ineffective. ...